Bromodomain and Extra-Terminal domain inhibitors for lymphoid malignancies. Issue 4 (July 2019) - Bertoni, Francesco; Stathis, Anastasios
Abstract : Purpose of review: Pharmacological inhibition of Bromodomain and Extra-Terminal (BET) domain proteins is a very exciting epigenetic therapeutic modality. Due to the central role of BET proteins in transcription regulation, their inhibition heavily affects lymphoma cells and BET inhibitors show a clear preclinical antitumor activity as single agents and in combination, paired with early reports of clinical activity. Recent findings: Relevant data have been recently presented on the mechanism of action of the BET inhibitors, on modalities to improve their activity in lymphomas, and their clinical evaluation. Summary: There are now plenty of preclinical data sustaining BET proteins as therapeutic targets in lymphomas. Newer compounds and combinations with other agents may be pursued in the future aiming also to identify those patients that they most likely benefit from BET inhibition.